Kontribusi Industri Gula Aren terhadap Pendapatan Rumah Tangga Petani di Desa Belimbing, Kecamatan Pupuan, Kabupaten Tabanan - SIMAMORA, SUSANNA E.R.; WIDYANTARA, I WAYAN; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.1, Januari 2020, 2020)
Contributions of Palm Sugar Industryon Farmers Household Income in Belimbing Village, Pupuan Sub-District, Tabanan Regency The palm sugar industry is one of the side livelihoods for most people in Belimbing Village. Belimbing Village is one of the villages in the Province of Bali that has been designated as the center of NIKOSAKE (Nira (palm sugar), Kopi (Coffee), Salak (Snake fruit), Kelapa (Coconut). This study aims to find out: 1) Sources of income of farmer households in Belimbing Village. 2) Contribution of palm sugar industry to the income of farmer households in Belimbing Village. The data analysis method used is quantitative and qualitative methods. This study shows that the source of income of farmer households in Belimbing Village, Pupuan Subdistrict, Tabanan Regency comes from palm sugar industry, farming (rice, coffee, durian, mangosteen, coconut, cocoa, bamboo, and banana), and non-farming ( traders and laborers). The results obtained, the average household income of palm sugar is Rp 5,062,162 per year, the average farm income is Rp 12,053,359 per year, and the average non-farm income is Rp 10,156,441 per year.